2022
DOI: 10.1302/0301-620x.104b3.bjj-2021-0894.r1
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic incidence significance relative to spinopelvic risk factors for total hip arthroplasty instability

Abstract: Aims Pelvic incidence (PI) is a position-independent spinopelvic parameter traditionally used by spinal surgeons to determine spinal alignment. Its relevance to the arthroplasty surgeon in assessing patient risk for total hip arthroplasty (THA) instability preoperatively is unclear. This study was undertaken to investigate the significance of PI relative to other spinopelvic parameter risk factors for instability to help guide its clinical application. Methods Retrospective analysis was performed of a multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…In this study, we found that the variables that were statistically associated with the risk of abnormal spinopelvic mobility before THA were a standing SPT≤-10°, IP-LL ≥ 20°, and LF ≥ 20°, which matched the actual literature; 5 , 7 , 19 however, if the univariate analysis showed that a stiff spine with an LF ≤ 20° was associated, it was not in the multivariate analysis. This result is probably due to the close relationship between SSD and spine stiffness.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In this study, we found that the variables that were statistically associated with the risk of abnormal spinopelvic mobility before THA were a standing SPT≤-10°, IP-LL ≥ 20°, and LF ≥ 20°, which matched the actual literature; 5 , 7 , 19 however, if the univariate analysis showed that a stiff spine with an LF ≤ 20° was associated, it was not in the multivariate analysis. This result is probably due to the close relationship between SSD and spine stiffness.…”
Section: Discussionsupporting
confidence: 64%
“…The outcome of interest was abnormal spinopelvic mobility, defined as ΔSPT ≥ 20° between the standing and relaxed-sitting positions. 7 We analyzed SPT≤-10°, LF ≤ 20°, PI-LL ≥ 20, PI ≤ 41°, SS < 35°, and the different groups of lordosis as risk factors in the overall population.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, tailoring the functional orientation of the component to the distinct phenotype of the patient is now fundamental when undertaking THA, in particular to avoid instability. 4-6…”
mentioning
confidence: 99%